The Rise of AI-Driven Marketing: Transforming Consumer Engagement in the Digital Era - Tanjung, Febrina Soraya; Hendarti, Fatimah Abdillah, Ricca (Pascasarjana STIE Amkop Makassar, 2025)
The rapid advancement of AI has revolutionized digital marketing, enabling businesses to enhance consumer engagement through data-driven insights, predictive analytics, and automation. This study explores the role of AI-driven marketing in transforming consumer interactions, focusing on personalization, communication effectiveness, and operational efficiency. Through qualitative research, including expert interviews and case studies, the findings reveal that AI enhances marketing performance by optimizing targeting strategies, improving customer experiences, and increasing return on investment (ROI). However, challenges such as data privacy concerns, algorithmic bias, and regulatory compliance pose significant ethical considerations. While AI-driven marketing offers substantial benefits, its long-term sustainability relies on responsible AI governance, transparency, and ethical best practices. This research contributes to the academic discourse on AI in marketing by providing insights into its applications, benefits, and potential risks, offering recommendations for businesses to maximize AI adoption while mitigating associated challenges. Keywords: AI-Driven Marketing, Consumer Engagement, Personalization, Predictive Analytics, Automation